Studies on Genetic Architecture Through Variability Parameters and Association Analysis in Cowpea [Vigna Unguiculata (L.) Walp.] (Bangladesh Journal of Botany, 2021)
Genetic architecture through variability parameters and association analysis for green forage yield and its characters in 78 germplasm lines including 3 checks (MFC-8-14, UPC-5286 and TSFC-12-15) was carried out during Rabi 2015-2016. All the fifteen studied characters exhibited existence of variability significantly. This indicated existence of sufficient variability among the genotypes for the mentioned characters and sufficient scope for development of new variety or genotypes. High genetic advances as percentage of mean were recorded for green forage yield (q/ha/day). High heritability estimates were recorded for 100-seed weight (g) and by green forage yield (q/ha). Correlation coefficient showed significant positive correlation with dependent character green forage yield with green forage yield per day at genotypic and phenotypic level. Maximum positive direct effect was obtained for green forage yield per day. These results indicate that green forage yield can be improved much better way by selection. Selection for these traits is likely to accumulate more additive genes leading to further improvement of performance of genotypes.Bangladesh J. Bot. 50(3): 557-564, 2021 (September)